Relationship Between Dividend Payout and Its Determinants: A Meta-Analysis - Saini, Divya; ., Surbhi; Sharma, Priti (Indian Journal of Finance, 2024)
Purpose : The main objective of this study was to statistically combine the outcomes of earlier literature on the relation between dividend pay-out and its determinants by utilizing the meta-analysis technique. Methodology : The analysis included independent characteristics such as size, age, leverage, EPS, cash flow, liquidity, return on assets, return on equity, and lagged dividends. Additionally, the payout of dividends was considered a dependent component. An evaluation of 56 research articles was conducted that emphasized the association between dividend pay-out and its determinants over the period from 2002–2023. The study employed Meta Essential software for meta-analysis of articles selected from the Web of Science and Scopus databases. Findings : The study found an affirmative correlation between dividend payout and ROA, ROE, EPS, cash flow, liquidity, age, size, and lagged dividend. Leverage had a detrimental correlation with dividend payouts. Practical Implications : The primary conclusion of the study was that it synthesized all of the research on the relationship between dividend payout and its variables, which had an impact on policymakers’ decisions and future research. It provides a comprehensive framework that will be useful to investors, corporations, and company regulators. Fisher’s Z transformation, which includes all the studies, can be used to do additional research. Originality : This study extends previous research by using meta-analysis to evaluate the relationship between dividend payout and numerous intrinsic, independent characteristics.